Insight into the microbial diversity and community in the sacrificial pits of Sanxingdui site (Sichuan, China) - Chen, Ruru; Xie, Zhenbin; Xiao, Qing; Wang, Chong; Wen, Rui (Frontiers in Microbiology, 2024)
IntroductionThe Sanxingdui site (Sichuan, China) is the typical representative of the ancient Shu culture, which lasts from the late Neolithic to early Western Zhou. The sacrificial pits are located in the core region of Sanxingdui site, and numerous artifacts are unearthed including ivory, seashells, bronzes, pottery, jade, stone, gold, bone, and horn products. The function of the pits and buried artifacts has always been the focus, but the microbiome around artifacts attracts less attention. Recently, the microbiome in buried ivory soil has just been identified; however, the microbiome around other artifacts has never been studied. In term of the unique perspective for interpretation the archaeological issues, the study was carried out for: (1) the microbial diversity and community of soil in the lower layer of artifacts in sacrificial pits, (2) the potential biodeterioration behavior of organic and inorganic relics, and (3) the impact of sacrificial and burial activities in different sacrificial pits on microbiome.MethodsThere were 45 soil samples around different artifacts in three sacrificial pits and 12 raw soil samples inside or outside the sacrificial pit sampling from Sanxingdui site. The microbial genomes were then identified and analyzed using the next-generation high-throughput sequencing.ResultsThe represented bacterial phyla were Proteobacteria, Actinobacteriota, GAL15, Chloroflexi, Acidobacteriota, Methylomirabilota, Thermoplasmatota, Crenarchaeota, Gemmatimonadota, and Firmicutes, and the represented fungal phyla were Ascomycota, Mortierellomycota, and Basidiomycota. Further microbial functional analysis found that the bacterial genera Sphingopyxis, Limnobacter, and Streptomyces and the fungal genera Cladosporium, Acremonium, and Mortierella were concerned with the degradation of organic matter, while the genera Pseudomonas, Arthrobacter, Variovorax, Aspergillus, and Penicillium might be related to the biocorrosion of bronzes. In addition, the microbial composition and principal co-ordinate analysis (PCoA) demonstrated the significant differences in microbial composition and structure between the raw soil samples and the soil samples around the artifacts and also between the soil samples in different sacrificial pits.DiscussionIt is important to understand the biodeterioration of the buried artifacts and the sacrificial activities in Sanxingdui site according to the results of microbial diversity and community. The combination of microbiology and archaeology will shed light on the archaeological issues related to the ancient human activities and behaviors.